128k views
5 votes
Given the function f(x) = 2|x + 6| – 4, for what values of x is f(x) = 6?

x = –1, x = 11
x = –1, x = –11
x = 14, x = –26
x = 26, x = –14

User R D
by
4.3k points

1 Answer

1 vote

Answer:

x = -1 , - 11,

Explanation:

| x | = x

|- x | = x

f(x) = 2 | x + 6 | - 4

x = - 1 , f( - 1) = 2 | - 1 + 6 | - 4 = 2 | 5 | - 4 = 10 - 4 = 6 , True

x = 1 , f( 1 ) = 2 | 1 + 6 | - 4 = 2 | 7 | - 4 = 14 - 4 = 10 , False

x = 11, f( 11 ) = 2 | 11 + 6 | - 4 = 2 | 17 | - 4 = 34 - 4 = 30 , False

x = - 11, f( - 11) = 2 | -11 + 6 | - 4 = 2 | - 5 | - 4 = 10 - 4 = 6 , True

x = 14 , f( 14 ) = 2 | 14 + 6 | - 4 = 2 | 20 | - 4 = 40 - 4 = 36 , False

x = -14 , f( - 14 ) = 2 | - 14 + 6 | - 4 = 2 | - 8 | - 4 = 16 - 4 = 12 , False

x = - 26 , f( - 26) = 2 | -26 + 6 | - 4 = 2 | -20 | - 4 = 40 - 4 = 36 , False

x = 26, f( 26 ) = 2 | 26 + 6 | - 4 = 2 | 32 | - 4 = 64 - 4 = 60 , False

OR

Given f ( x ) = 6

f( x ) = 2 | x + 6 | - 4

6 = 2 | x + 6 | - 4

6 + 4 = 2 | x + 6| - 4 + 4 [ adding 4 to both sides ]

10 = 2 | x + 6 | + 0

5 = | x + 6 | [ dividing both sides by 2 ]


- 5 =\ ( x+ 6) \ = 5\\\\
[ \ | x | = a\ => \ -a \ = x \ = a \ ]


- 5 - 6 = \ x + 6 - 6 \ = \ 5 - 6\\
[ \ subtracting \ by \ 6 \ ]


-11 = \ x \ = - 1

User LiriB
by
4.8k points